Solution for Providing Ruminant Feed during the Dry Season in Pesisir Selatan Regency using Ammonia-treated Rice Straw - Afriani, Tinda; Khasrad; Hafizah, Dian; Fadhilah, Ade (Warta Pengabdian Andalas, 2025)
The potential of rice straw in Pesisir Selatan Regency can be utilized to ammoniate straw as a solution to providing feed for ruminants. The abundance of agricultural waste can address livestock problems in Pesisir Selatan Regency during the dry season. The dry season makes the availability of forage stocks low. Through fermentation in ammoniation technology, straw waste can be used. The activity began with discussion, socialization, demonstration, and evaluation of the activity results. Fermented feed, such as straw ammoniation, has advantages and disadvantages. Ammoniated straw can increase digestibility, nutritional value, and long shelf life. The characteristics of good ammoniated straw are that it turns brownish yellow or does not change much from the color of the straw, when opened, it smells quite pungent of ammonia, the texture of the rice straw is soft, not rotten, and not moldy. Ammoniation as an alternative feed has high potential in supporting healthy and efficient livestock production. Community Service activities are an important step in encouraging sustainable agriculture and livestock.